Case Report: Single-port thoracoscopic surgery for severe primary palmar hyperhidrosis in a 9-year-old child - Luo, Zhen; Li, Yu; Zhou, Guangxu; Mao, Kaiyi; Tan, Hongyang; Zhao, Peng; Li, Yingbo; Shang, Xianhui; Ma, Hong; Wang, Cao (Frontiers in Medicine, 2025)
Primary palmar hyperhidrosis (PPH) is a somatic condition characterized by excessive sweating of the hands. It mainly affects adolescents and young adults and is rarely observed among children. This condition significantly impairs patients' academic performance, daily activities, and social interactions and can even lead to insurmountable psychological burdens. Surgical intervention for PPH is typically reserved for individuals aged 16 years and older, as compensatory hyperhidrosis occurs at a high rate (65%) postoperatively among children younger than 14 years. Therefore, the decision for surgery is controversial and has been rarely documented in the literature. Here, we report a 9-year-old child with a 3-year history of bilateral palmar hyperhidrosis. Conservative treatment with medications for 6 months led to no improvement. The patient had signs of low self-esteem, social withdrawal, and aversion to school, alongside recurrent skin damage at the fingertips. Both the child and parents expressed a strong desire for effective treatment. Single-port endoscopic thoracic sympathectomy (ETS) was conducted after comprehensive risk disclosure and obtaining informed consent from the parents, achieving remarkable therapeutic outcomes. At the 12-month follow-up, the patient exhibited no recurrence of symptoms, no compensatory hyperhidrosis, and no complications, such as Horner's syndrome. Both hands remained warm and dry, the lesions of fingertip skin healed, and the patient's personality became noticeably more positive. Furthermore, the surgical incision was aesthetically pleasing.